Current Issues Affecting the Practice of Pediatric Orthopaedic Surgeons: Results of the 2014 Workforce Survey of American Academy of Pediatrics Section on Orthopaedics. Issue 1 (January 2018) - Hosseinzadeh, Pooya; Copley, Lawson; Ruch-Ross, Holly; Schwend, Richard M.; Sawyer, Jeffrey R.
Abstract : Introduction: The opinions of the pediatric orthopaedic workforce are shaped by market forces, regulatory processes, and local experience. The purpose of this report is to summarize the findings of the recent Workforce Survey of the American Academy of Pediatrics (AAP) Section on Orthopaedics (SOOr). This submission has been reviewed and approved by the Board of Directors of the Pediatric Orthopaedic Society of North America (POSNA). Methods: In 2014, the AAP generated a survey to assess perceptions of pediatric orthopaedic surgeons about current issues that affect practice. The survey was sent to 856 POSNA and 141 AAP-SOOr members. Responses were topically organized to report current workforce composition, practice patterns, and perceptions about electronic medical records (EMRs). Results: Responses were collected from August to December, 2014, from 496 (50%) survey recipients including 83 of 141 (59%) AAP-SOOr members and 413 of 856 (48%) POSNA members. Analyses were restricted to the 397 respondents who reported that they are currently practicing pediatric orthopaedics. Nearly all of these (390/391, 100%) indicated that they provide direct patient care and work an average of 60 hours per week. Many (105/378, 28%) indicated that they would soon limit their practice or retire. A majority (299/394, 76%) indicated that they face competition in their geographic area, predominantly due to pediatric orthopaedic subspecialists (269/299, 90%). Major business changes had recently occurred or were anticipated by 21% of participants. Respondents reported that use of EMR makes them less efficient (252/397, 63%) and interferes with the patient-physician relationship (172/397, 43%). Discussion: This workforce survey suggests that pediatric orthopaedic surgeons are concerned with challenges of competition despite concurrent increasing volume and complexity of referrals. External processes such as EMR changes are perceived to negatively impact practice efficiency and satisfaction.